A systematic literature review of the causal framework of personal news curation on social media - Yujing, Chu; Mohd Zawawi, Julia Wirza; Bidin, Rosmiza (Redfame Publishing, 2024)
The changing hierarchical relationship between mass media consumers and media content producers in the information age has given rise to extensive research on personal news curation. This study presents a systematic overview of previous studies on social media users' personal news curation practices. In the study of personal news curation practices on social media, gaps in themes, theories, variables, and conceptual frameworks are to be found and filled by means of this systematic review of the literature. The goal of the study is to provide a causal framework that illustrates the connections between the various research items.Twenty papers that were taken from the Scopus, Google Scholar and Web of Science databases are reviewed using the PRISMA method. Two main study themes, fifteen theories or models, and a comprehensive causality framework emerged from the examination.We recommend that future research on the personal news curation practices provide empirical studies on different types especially the personal productive news curation on social media, widen the field of research and adopt different theories or models according to the new social media environments and contexts. Researchers are also expected to adopt a more complete and detailed systematic approach to review the literature on the study of personal news curation on social media.